2021
DOI: 10.3390/microorganisms10010090
|View full text |Cite
|
Sign up to set email alerts
|

Serbian Traditional Goat Cheese: Physico-Chemical, Sensory, Hygienic and Safety Characteristics

Abstract: This research project aimed to investigate the physico-chemical, sensory, hygienic and safety characteristics of raw goat milk, whey, brine and traditional goat cheese during the ripening period of 28 days. Physico-chemical parameters included the determination of dry matter, fat, ash, protein, pH, water activity and NaCl content. The presence of Enterobacteriaceae and fungi was estimated on milk and cheese samples, and a sensory panel evaluated the products’ features and acceptability during ripening. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The best-evaluated characteristic of the goat cheese was its white colour, and no atypical colour spots could be observed. The results of this study are consistent with the findings of Mladenović et al (2021) who examined traditional white-brined goat cheeses, except that no bitterness was observed.…”
Section: Mufa -Monounsaturated Fatty Acids; Sscfa -Saturated Short-ch...supporting
confidence: 91%
See 2 more Smart Citations
“…The best-evaluated characteristic of the goat cheese was its white colour, and no atypical colour spots could be observed. The results of this study are consistent with the findings of Mladenović et al (2021) who examined traditional white-brined goat cheeses, except that no bitterness was observed.…”
Section: Mufa -Monounsaturated Fatty Acids; Sscfa -Saturated Short-ch...supporting
confidence: 91%
“…05) with the results of Bodnár et al (2021) and Pajor et al (2021) for semi-hard goat cheese. Comparing both groups of experimental cheese samples, it was found that dry matter, protein, and NaCl content were higher than in traditional goat white-brined cheese (Mladenović et al, 2021). In particular, fat content was higher in pasture-raised cheese.…”
Section: Mufa -Monounsaturated Fatty Acids; Sscfa -Saturated Short-ch...mentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the air-ripened cheeses had the highest color intensity in cross-section and rind thickness, which may be due to the fact that these cheeses had the lowest moisture content compared to the cheeses ripened in oil after 10 or 20 days of ripening in the air [23], and it is well known that greatest moisture loss occurs at the beginning of ripening [23,46,47]. In the study of traditional Serbian goat cheese, the most pronounced changes in cheese color (yellowing) occurred after 14 days of ripening, which was due to moisture loss, the microbiological activity of non-starter lactic acid culture, and complex biochemical processes (proteolysis, lipolysis, and oxidation processes) [48]. The results for the color parameters (yellowness) in the study of Serrana goat cheese, which was subjected to a particularly long ripening period, were explained by a slight browning effect typical of cheese ripening [49].…”
Section: Resultsmentioning
confidence: 99%
“…1,6 Antibiotics are usually administered as a prophylactic measure to reduce disease or bacteriological spoilage-related losses of products both on the farm and in the live animal market, without considering withdrawal periods. 7 Consequently, a significant amount of the applied antibiotics remains in the food chain as residue. 8 This situation is common in many least developed and developing countries, where agricultural farming has increased in step with socio-economic development.…”
Section: Introductionmentioning
confidence: 99%